Increased levels of prostaglandin E−major urinary metabolite (PGE-MUM) in chronic fibrosing interstitial pneumonia. (January 2017) - Horikiri, Tsugumi; Hara, Hiromichi; Saito, Nayuta; Araya, Jun; Takasaka, Naoki; Utsumi, Hirofumi; Yanagisawa, Haruhiko; Hashimoto, Mitsuo; Yoshii, Yutaka; Wakui, Hiroshi; Minagawa, Shunsuke; Ishikawa, Takeo; et al.
Abstract: Background: Dysregulation of the prostaglandin E2 (PGE2) signaling pathway has been implicated in interstitial pneumonia (IP) pathogenesis. Due to the unstable nature of PGE2, available detection methods may not precisely reflect PGE2 levels. We explored the clinical usefulness of measuring stable prostaglandin E−major urinary metabolite (PGE-MUM) with respect to pathogenesis and extent of chronic fibrosing IP (CFIP), including idiopathic pulmonary fibrosis (IPF), as PGE-MUM is reflective of systemic PGE2 production. Methods: PGE-MUM was measured by radioimmunoassay in controls (n = 124) and patients with lung diseases (bronchial asthma (BA): n = 78, chronic obstructive pulmonary disease (COPD): n = 33, CFIP: n = 44). Extent of lung fibrosis was assessed by fibrosing score (FS) of computed tomography (CT) (FS1-4). Immunohistochemical evaluation of COX-2 was performed to find PGE2 producing cells in IPF. Human bronchial epithelial cells (HBEC) and lung fibroblasts (LFB) were used in in vitro experiments. Results: Compared to control, PGE-MUM levels were significantly elevated in CFIP. PGE-MUM levels were positively correlated with FS, and inversely correlated with %DLCO in IP (FS 1–3). COX-2 was highly expressed in metaplastic epithelial cells in IPF, but lower expression of EP2 receptor was demonstrated in LFB derived from IPF. TGF-β induced COX-2 expression in HBEC. Conclusions: PGE-MUM, elevated in CFIP, is a promising biomarker reflecting disease activity. Metaplastic epithelial cells can be a source of elevated PGE-MUM in IPF. Highlights: PGE-MUM were elevated in chronic fibrosing interstitial pneumonia(CFIP). PGE-MUM levels were correlated with lung function in CFIP. Metaplastic epithelial cells can be a source of elevated PGE-MUM in IPF.